Physician-patient communication in the prevention of female reproductive tract infections: some limitations Comunicação entre médicos e mulheres na prevenção das infecções do trato reprodutivo: algumas limitações - María Y. Makuch; Neury José Botega; Luis Bahamondes (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2000)
The objective of this study was to describe the information that women with tubal infertility recalled having received from physicians when they consulted for a reproductive tract infection (RTI) and the information physicians reported having provided to women consulting for RTIs. Interviews were conducted with 16 women presenting primary tubal infertility selected on the basis of purposeful sampling criteria. Also, 15 physicians working in the public health network in the city of Campinas, Brazil, were selected at random and interviewed. Analysis of the women's statements concerning previous RTI-related medical consultations showed that they did not recall having received any information on either prevention or the impact of RTI on their reproductive future. Analysis of interviews with physicians showed that the information they provided to women consulting for RTIs was incomplete and unclear. The information women recalled having received and that which physicians remembered having provided at the time of treating a patient with RTI was similar. In conclusion, these women lacked adequate or complete information and that it was probably not possible for them to adopt measures to avoid repetition of RTI and minimize risk of tubal infertility. O objetivo deste estudo foi descrever a informação que mulheres com esterilidade tubária lembravam haver recebido dos médicos quando elas compareceram à consulta em virtude de infeções do trato reprodutivo (ITR), assim como a informação que os médicos referiram dar-lhes no momento da consulta. Foram entrevistadas 16 mulheres com esterilidade primária de causa tubária, selecionadas seguindo o critério de amostra proposital. Foram selecionados ao acaso e entrevistados 15 médicos da rede pública de Campinas, SP, Brasil. A análise das respostas das mulheres mostrou que elas não lembravam de ter recebido informação a respeito de meios de prevenção ou sobre o impacto das ITRs em seu futuro reprodutivo. A análise das entrevistas com os médicos revelou que a informação que eles declararam prover às mulheres em questão sobre as formas de transmissão, os riscos para o futuro reprodutivo e meios de prevenção foi incompleta ou pouco clara. A informação que as consulentes lembravam haver recebido e a que os médicos referiram dar sobre as ITR foi similar. Em conclusão, essas mulheres não receberam informação adequada ou completa, e provavelmente não foi possível que implementassem meios de prevenção para evitar a repetição de ITR e minimizar o risco de esterilidade tubária.